Web-based Support Systems - Yao, JingTao (Advanced Information and Knowledge Processing, 2010)
Web-based Support Systems (WSS) are an emerging multidisciplinary research area in which one studies the support of human activities with the Web as the common platform, medium and interface. One of the goals of WSS research is to extend the human physical limitation of information processing in the information age. Research on WSS is motivated by the challenges and opportunities arising from the Internet. The availability, accessibility and flexibility of information as well as the tools to access this information lead to a vast amount of opportunities. It identifies both domain independent and dependent activities before selecting suitable computer and Web technologies to support them. It also examines how applications and adaptations of existing methodologies on the web platform benefit our decision-making and other various activities. This book presents research related to fundamental issues of WSS, frameworks for WSS and current research on WSS. The research on Web-based support systems is classified into three parts: - Web-based support systems for specific domains - Web-based applications and WSS techniques - Design and Development of WSS.